Biometric classification system for dorsal finger creases utilizing multi-block circular shift combination local binary pattern - Riaz, Imran; Ali, Ahmad Nazri; Ibrahim, Haidi; Huqqani, Ilyas Ahmad (International Journal of Electrical and Computer Engineering (IJECE), 2024)
In recent years, there has been a growing interest in biometric recognition based on finger dorsal patterns, making it a significant area of research. This paper introduces a biometric classification system that utilizes dorsal finger middle creases. The viability of this trait is assessed through the implementation of a new method known as multi block circular shift combination local binary pattern (MBCSC-LBP). The MBCSC-LBP approach involves dividing the image into multiple blocks to enhance robustness and capture both local and global information, thereby extracting discriminative features. These features from each block are then concatenated to form a comprehensive feature vector. To evaluate the accuracy of the proposed MBCSC-LBP feature extractor, a support vector machine (SVM) with a linear kernel is utilized. The classification accuracy achieved by this method is 96.22% indicating a promising performance.